If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6b + 1)(2b + -4) = 0 Reorder the terms: (1 + 6b)(2b + -4) = 0 Reorder the terms: (1 + 6b)(-4 + 2b) = 0 Multiply (1 + 6b) * (-4 + 2b) (1(-4 + 2b) + 6b * (-4 + 2b)) = 0 ((-4 * 1 + 2b * 1) + 6b * (-4 + 2b)) = 0 ((-4 + 2b) + 6b * (-4 + 2b)) = 0 (-4 + 2b + (-4 * 6b + 2b * 6b)) = 0 (-4 + 2b + (-24b + 12b2)) = 0 Combine like terms: 2b + -24b = -22b (-4 + -22b + 12b2) = 0 Solving -4 + -22b + 12b2 = 0 Solving for variable 'b'. Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -11b + 6b2) = 0 Factor a trinomial. 2((-1 + -6b)(2 + -1b)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -6b)' equal to zero and attempt to solve: Simplifying -1 + -6b = 0 Solving -1 + -6b = 0 Move all terms containing b to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -6b = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -6b = 0 + 1 -6b = 0 + 1 Combine like terms: 0 + 1 = 1 -6b = 1 Divide each side by '-6'. b = -0.1666666667 Simplifying b = -0.1666666667Subproblem 2
Set the factor '(2 + -1b)' equal to zero and attempt to solve: Simplifying 2 + -1b = 0 Solving 2 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1b = 0 + -2 -1b = 0 + -2 Combine like terms: 0 + -2 = -2 -1b = -2 Divide each side by '-1'. b = 2 Simplifying b = 2Solution
b = {-0.1666666667, 2}
| 2x^2+2y^2+4xy-4=0 | | (9c/10b)/(3c/2b^3c4)= | | 9c/10b= | | 30=67t-5t^2 | | 0.53KG=XG | | 2ln(r)=ln(15r+34) | | 0=130-6t-16t^2 | | 2(3X-2)=4x-14 | | 21=5+34t-16t^2 | | -3+.5y=4x+11 | | f(0)=4x-16 | | 2(u-4)-7u=-13 | | 2y-4+xy-2x= | | 7.6x-2=6.6x | | 9+2x=y+3 | | 7x+4-3+12= | | x/4-0.5=6 | | x/5-0.5=6 | | 3n-4-5n+6=-8 | | p-2/4=3 | | 4/3y=24 | | (w-7)(3w+7)=0 | | 3*0-6y=12 | | 5(x+4)-2(x-3)= | | p-5/4=3 | | t/5-6=7 | | 31n(x+6)=9 | | (a-4)(5a+3)(a+4)= | | 12=160-12t-16t^2 | | 80,000.00+209.00x=599.00x. | | x/5=9/6 | | (24000-x)*(17600/x)=1600 |